A descriptive study on the awareness and utilization of caries preventive measures by caregivers of children with special health care needs in cts - Palma Gil, Ma. Andrea C.
Children with Special health care needs (SHCN) are at greater risk of acquiring oral health problems than the general population. SHCN children are more likely to have unmet dental needs than any other medical need. This could be attributed to several factors. However, the most common is the limited or lacking oral health literacy of caregivers of children with special health care needs. This study aims to describe and determine the level of awareness and utilization of caries preventive measures by caregivers of children with SHCN at the College of Allied Medical Profession - Clinic for therapy services (CAMP-CTS), UP Manila. The researchers conducted a survey using a three-part self-administered questionnaire as a means of gathering data and applied descriptive and inferential statistics in analyzing the data gathered. The study compares the association between the level of awareness with the level of utilization among the study population. The association between the level of awareness and utilization with factors like age, educational attainment, monthly income, family size and sources of information on Caries Preventive Measures (CPM) were also determined. Based on the results of this study, majority of the caregivers had moderate levels on both awareness (55.71%) and utilization (52.14%). None of the caregivers had high awareness level while only 3.57% marked high in the utilization level. It was also concluded in this study that the higher level of awareness among caregivers of SHCN patients will not necessarily lead to a higher level of utilization of caries preventive measures.